1982
DOI: 10.1152/ajpendo.1982.243.5.e365
|View full text |Cite
|
Sign up to set email alerts
|

Central infusion of vasopressin decreased plasma vasopressin concentration in dogs

Abstract: The effects of increasing the cerebrospinal fluid (CSF) vasopressin concentration (CSFADH) by intracerebroventricular infusion of vasopressin on the plasma vasopressin concentration (PADH) were studied in four groups of anesthetized dogs. One group received an intracerebroventricular infusion of artificial CSF (ACSF) alone for 90 min; the other groups were infused intracerebroventricularly with vasopressin at rates of 10, 20, or 50 microunits/min for 90 min. Arterial blood and CSF samples were taken just befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1984
1984
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Functional evidence suggests that the effects of vasopressin on electrical activity are likely to be inhibitory. Intracerebroventricular injection of vaso-Vasopressin effects on supraoptic nucleus neurons 2533 pressin decreases plasma vasopressin concentration (Wang et al, 1982), while V I N Z antagonists enhance vasopressin release into the blood in response to osmotic stimulation (Liu et al, 1996), but the site of action of vasopressin cannot be inferred from these experiments.…”
Section: Introductionmentioning
confidence: 97%
“…Functional evidence suggests that the effects of vasopressin on electrical activity are likely to be inhibitory. Intracerebroventricular injection of vaso-Vasopressin effects on supraoptic nucleus neurons 2533 pressin decreases plasma vasopressin concentration (Wang et al, 1982), while V I N Z antagonists enhance vasopressin release into the blood in response to osmotic stimulation (Liu et al, 1996), but the site of action of vasopressin cannot be inferred from these experiments.…”
Section: Introductionmentioning
confidence: 97%
“…It has been reported that vasopressin administered cen trally causes a decrease in the plasma concentration o f va sopressin [14]. This indicates that vasopressin occurring within the central nervous system may be able to alter its own release into the circulation.…”
Section: Discussionmentioning
confidence: 99%
“…It seems likely, therefore, that under the conditions o f the present experiment there is probably no negative feedback inhibition by vasopressin on its own release. Thus, the reduction in plasma vasopressin concentration induced by the central administration of this hormone [14] is caused by an action of vasopressin at sites remote from areas that would be affected by circulating hormone. Fur thermore, it is likely that the only way that circulating vaso pressin can alter its own release is in a long negative feed back loop involving its actions on blood pressure, blood vo lume, and plasma osmolality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In several studies, therefore, the effect of central administration of AVP on body water metabolism has been examined. A central dipsogenic effect of centrally applied AVP has been reported (Szczepanska-Sadowska, Sobocinska & Sadowski, 1982) and release of pituitary AVP was shown to be inhibited following intracerebroventricular injection or infusion of AVP (Bhargava, Kulshrestha & Srivastava, 1977;Wang, Share & Crofton, 1982). However, in other studies no effects of such AVP treatments have been found on peripheral hydration and consummatory behaviour (Severs, Keil & Klase, 1978;Jerome, Barbella, Wurpel et al 1983).…”
mentioning
confidence: 99%